PEMBUATAN ES KRIM DENGAN PENAMBAHAN TEH KOMBUCHA SEBAGAI SUMBER ANTIOKSIDAN - Pangestu, Dio Ajie; Yusmarini, Yusmarini Yusmarini; Restuhadi, Fajar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aimed to know the characteristics quality and sensory ice cream with the addition of different concentration of kombucha tea, as well as to know the best formulation that fulfill’s SNI (01-3713-1995). The research was conducted with five treatments and three replications. The treatments in this study were kombucha tea addition of 0, 10, 20, 30, and 40%. Data were statistically analyzed by using analysis of variance and followed by duncan ‘s new multiple range test at level 5%. The result of analysis of variance showed that the addition of kombucha tea significantly affected total dissolved solid, fat level, sucrose level, and antioxidant but did not significantly affect protein level. Kombucha tea ice cream treatment selected from the tested parameters was the treatment T2 (addition of 20% kombucha tea). The ice cream obtained had a fat 15.58%, protein 3.72%, sucrose 10.37%, total solids 30.22%, antioxidants 56.48 ppm.Keywords: ice cream, kombucha tea, antioxidant.